2022
DOI: 10.3389/fphar.2022.981799
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on microRNA in gout

Abstract: Gout is a common form of arthritis caused by the deposition of sodium urate crystals in the joints and tissues around them. MicroRNAs (miRNAs) are noncoding RNAs that have been shown to be involved in regulating the pathogenesis of gout through multiple cellular signaling pathways, which may be potential targets for the treatment of gout. In this review, we systematically discuss the regulatory roles of related miRNAs in gout, which will provide help for the treatment of gout and miRNAs is expected to become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Studies have shown that some miRNAs are involved in both hyperuricemia and gout ( 22 , 67 ). For example, the expression of miR-146a was significantly increased in patients with gout and involved in both NLRP3 and MyD88/NF-κB pathways ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some miRNAs are involved in both hyperuricemia and gout ( 22 , 67 ). For example, the expression of miR-146a was significantly increased in patients with gout and involved in both NLRP3 and MyD88/NF-κB pathways ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the stem shape of the hydroponic Chinese kale is approximately cylindrical, it was assumed to be an elastic body with transverse isotropy. The constitutive stress-strain relationships were established by Formulas (1) to (8) [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Hydroponic Chinese kale is one of the clean, short-growth cycles, and high-value leaf vegetables widely planted in the southern China facility enterprise [1][2][3]. Currently, fresh hydroponic Chinese kales are harvested by being grabbed out of the pipeline and root cut using the manual method, which leads to high labor intensity and cost problems [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are other, non-canonical pathways for miRNA production. These include so-called “mirtrons”, spliced introns of mRNA, fully Dicer-independent miRNA which is derived from endogenous shRNA processed by Drosha and cleaved by hAgo2 (Human Protein argonaute-2) or m7g (7-methylguanosine)-capped pre-miRNA that can be exported to the cytoplasm without Drosha cleavage [ 58 , 59 , 60 ]. In many cases, multiple miRNAs are transcribed as one long transcript (cluster) that is subsequently cleaved.…”
Section: Nucleic Acids In Rnaimentioning
confidence: 99%